Faktor Pembentuk Brand Love, Word Of Mouth, Dan Repurchase Intention Atas Produk Hedonis: Telaah Pada Pelanggan Produk Gunpla Merek Bandai - Aditya Tri Nugroho; Whony Rofianto; Surachman Surjaatmadja; Meta Andriani (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to analyze the factors that influence brand love, as well as its implications for word of mouth, and repurchase intention. Rooted in the theory of interpersonal love and relationships, this research is an expansion of previous research models by accommodating aspects of brand community, brand experience and price perception. Empirical data was collected through an online survey of 100 samples of Bandai Gunpla consumers living in Indonesia. Hypothesis testing is done through Partial Least Square Structural Equation Modeling (PLS-SEM) approach. Based on the estimation of the structural model that has been carried out, the results show that self-expressiveness has a positive effect on brand love, brand trust has a positive effect on brand love, brand community has a positive effect on brand love, brand love has a positive effect on WOM and e-WOM, brand love has a positive effect on repurchase intention and brand experience has a positive effect on repurchase intention. Meanwhile, the hypothesis of the positive effect of hedonic products on brand love and price perception on repurchase intention was not proven in this study.